Mahar Uang Hiasan Menurut Perpektif Madzhab Imam Syafi’i dan Imam Hanafi - Janna, Sirojul; al-Amin, Habibi (Menara Tebuireng, 2023)
This research is a qualitative field research. The author used three data collection techniques to obtain data, namely interviews, observation and documentation. The author uses data analysis techniques in the form of objective interpretations. The conclusion from the general research is that giving a dowry of decoration is permissible as long as it has economic value. Giving dowry in the form money, goods or services must have benefits for the life of his wife, including fulfilling the dowry requirements in Islamic law. The majority of married couples use dowry money as a symbol of marriage to make it look more impressive and unique. Imam Asy-syafi’I defines dowry as something that is obligatory because of marriage or intercourse, or the passing of a woman’s honor without power, such as the result of breastfeeding and the without al of witnesses. According to imam syafi’I the complete pillars of marriage are as follows: prospective wife, prospective husband, 2 witnesses, guardian, shighat. According to imam Hanafi, dowry is giving a number of assets which are the rights of the wife, because of marriage ties or because of different types of sexual relation based on Islamic law. The imam Hanafi school of are the right of the wife, due to a marriage contract, or due to actual intercourse. Meanwhile, according to imam malik, dowry is the cause and effect of the halal relationship between husband and wife. Imam hambali’s opinion is that dowry is a reward for a marriage, whether it is stated clearly in the marriage contract, determined after the contract is agreed upon by both parties, or determined by the judge. Keyword: dowry money decoration